The Effect of Training, Development, and Innovative Work Behaviour on Employee Performance in the Heavy Equipment Industry - Aditya Dwi Septyanur; Jordan Michael Sukanda; Muhammad Zaenul Ihsan Majdi; Syarifa Hanoum; Ummi Naiemah Saraih (International Journal of Business and Management Technology in Society, 2023)
Abstract Purpose – The study aims to determine the impact of training, development, and innovative work behavior on employee performance in the heavy machinery industry. Methodology – This study employs an explanatory approach using a logistic regression model with data collected through questionnaires from 79 respondents working in a heavy machinery industry in Indonesia. The variables studied include training, development, and innovative work behavior as independent variables, and employee performance as the dependent variable. Findings – The results show that training and development have a significant positive effect on employee performance (p < 0.05), while innovative work behavior does not show a statistically significant impact (p > 0.05). The Nagelkerke R Square value indicates that 23.2% of the variance in employee performance can be explained by the model. Practical implications – From findings suggest that companies should focus on improving training and development programs to enhance employee performance. Meanwhile, efforts to foster innovative behavior may require a reevaluation of current strategies and organizational support mechanisms.